2019
DOI: 10.1002/agr.21626
|View full text |Cite
|
Sign up to set email alerts
|

Is there hope for domestically produced poultry meat? A choice experiment of consumers in Ghana

Abstract: Over the past few decades, the opening up of trade has often put producers in developing countries under competitive pressure from food imports, particularly in the case of poultry products. Consequently, raising numerous concerns about the continued growth of domestic poultry production, especially in sub‐Saharan Africa. Therefore, this paper assesses consumers’ preferences and willingness to pay for chicken meat of domestic and imported origins and other quality attributes. We used data conducted among 500 c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 41 publications
0
10
0
Order By: Relevance
“…In countries where the population consumes and imports large quantities of meat, veterinary antimicrobial sales data can help inform consumers about the safety of their food and potentially increase market preference for production systems using less antimicrobials [ 23 , 24 , 25 ]. Reporting antimicrobial sales data can help guide policymakers in regulating animal product imports coming from countries that use large quantities of antimicrobials and that may contain antimicrobial resistant bacteria and antimicrobial residues.…”
Section: Introductionmentioning
confidence: 99%
“…In countries where the population consumes and imports large quantities of meat, veterinary antimicrobial sales data can help inform consumers about the safety of their food and potentially increase market preference for production systems using less antimicrobials [ 23 , 24 , 25 ]. Reporting antimicrobial sales data can help guide policymakers in regulating animal product imports coming from countries that use large quantities of antimicrobials and that may contain antimicrobial resistant bacteria and antimicrobial residues.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have indicated that consumers pay attention to food products with production claims, including production systems, production methods and processing methods [60][61][62][63][64]. Asante-Addo and Weible [65] reported that consumer utility increases when an antibiotic/hormone-free claim is made for a meat product. Yang et al [66] found that consumers prefer the production claim "Wild" rather than "Farmed" when they assessed consumer willingness to pay for Arctic food products.…”
Section: Discussionmentioning
confidence: 99%
“…As a way of dealing with the dwindling fortunes of the local broiler industry, the government of Ghana and other stakeholders have implemented several initiatives to revamp the poultry sector and increase meat production in the country (Ghana Poultry Project (GPP), 2016). A recent study by Asante-Addo and Weible (2019) reveals that there is a preference for domestically produced chicken to imported chicken. Other studies have been undertaken in the poultry industry and specifically, the broiler sub-sector and have confirmed the profitability of domestic meat production (Asuming-Brempong et al, 2006;Dziwornu, 2014;Etuah, 2014), availability of organized markets and consumers' desire for convenience (Adei and Asante, 2012;Woolverton & Frimpong, 2013).…”
Section: Study Background and Rationalementioning
confidence: 99%